2011
DOI: 10.1159/000326693
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Acting Methylphenidate in Adults with Attention Deficit Hyperactivity Disorder: A Study with Paired-Pulse Transcranial Magnetic Stimulation

Abstract: Background: Methylphenidate improves attention deficits, hyperactivity and impulsivity in attention deficit hyperactivity disorder (ADHD). Recent investigations into motor cortex excitability with paired-pulse transcranial magnetic stimulation (ppTMS) technique have shown inhibition deficits in ADHD which correlate with clinical symptomatology. Therefore, we investigated the neurophysiological effects of long-acting methylphenidate (LA-Mph) with the ppTMS technique in adult patients with ADHD. Methods: Thirtee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…In particular, a therapeutic study that observed improvements in ADHD symptoms reported normalization of dACC activation following multiple NFB sessions (Lévesque et al 2006). Likewise, the noradrenergic stimulant methylphenidate has been seen to increase dACC activation (Rubia et al 2011) and cortical disinhibition (Schneider et al 2011) in proportion to the clinical response of patients with attentional deficits. Intriguingly, in an earlier investigation we found that alpha desynchronization also leads to a lasting enhancement of cortical disinhibition (Ros et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a therapeutic study that observed improvements in ADHD symptoms reported normalization of dACC activation following multiple NFB sessions (Lévesque et al 2006). Likewise, the noradrenergic stimulant methylphenidate has been seen to increase dACC activation (Rubia et al 2011) and cortical disinhibition (Schneider et al 2011) in proportion to the clinical response of patients with attentional deficits. Intriguingly, in an earlier investigation we found that alpha desynchronization also leads to a lasting enhancement of cortical disinhibition (Ros et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…97 Methylphenidate enhances short-interval intracortical inhibition, which has also been reported with other medications that enhance dopaminergic neurotransmission. 73,80,98 101 Given that short-interval intracortical inhibition is correlated to hyperactivity, and methylphenidate normalizes short-interval intracortical inhibition and improves hyperactivity, it is possible that short-interval intracortical inhibition could be used as an objective and quantitative proxy of the therapeutic effectiveness of methylphenidate. There are a variety of potential uses for this information, such as identifying whether an individual has a greater change in short-interval intracortical inhibition with methylphenidate versus other ADHD medications, or as a way to identify methylphenidate nonresponders without the need for a prolonged medication trial.…”
Section: Noninvasive Brain Stimulation In Adhdmentioning
confidence: 99%
“…With children as well as with adults, MPH is extensively used in the treatment of ADHD. The substance is known to restore disturbed cortical motor inhibition and facilitation in children (Buchmann et al, ; Gilbert et al, ; Moll et al, ) and to improve motor disinhibition in adults (Schneider et al, ). Remarkably, contradictory results have been obtained for SICI and ICF in healthy adults after the ingestion of a single dose of MPH (Gilbert et al, ; Ilic, Korchounov, & Ziemann, ; Kirschner et al, ; Moll, Heinrich, & Rothenberger, ).…”
Section: Introductionmentioning
confidence: 99%